PERBANDINGAN KADAR D-DIMER PADA PASIEN CORONA VIRUS DISEASE 2019 (COVID-19) KOMORBID DAN NON KOMORBID DI RUMAH SAKIT RUJUKAN KHUSUS COVID-19 PEKANBARU - Panji Agung; Octariany Octariany (LPPM Universitas Abdurrab, 2023)
Background : Coronavirus disease 2019 (COVID-19) is a disease caused by betacoronavirus, an RNA virus genome, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Several specific markers are needed in assessing the severity of COVID-19, including D-Dimer. D-Dimer is a byproduct of the blood clotting and breakdown process that can be measured through analysis of a blood sample. D-Dimer is released when blood clots begin to break down. D-Dimer is widely used as an indicator of inflammation. In viral infections including COVID- 19, D-Dimer levels will quickly increase. The increase in D-Dimer in patients affected by COVID-19 is exacerbated by the presence of comorbidities. Comorbidity is the occurrence of several chronic or acute medical diseases or conditions in one individual. This research was conducted at Arifin Achmad Regional General Hospital which is a referral hospital that handles COVID-19 cases and has a treatment bed for COVID-19 cases which has an isolation room for COVID-19 patients.Objective: Analyze the comparison of D-Dimer levels of COVID-19 patients with and without comorbidities.Method: This study was a comparative quantitative analytical study with a Cross-sectional approach conducted to see the comparison of D-Dimer levels with COVID-19 patients with and without comorbidities, the samples used were 60 medical record data of patients confirmed with COVID-19 divided into 2 groups consisting of COVID-19 patients with comorbidities and without comorbidities, then bivariate analysis of the Mann whitney test was carried out.Results: The results showed that the most common types of comorbidities in COVID-19 patients were comorbid diabetes mellitus and hypertension. In COVID-19 patients with comorbidities, D-Dimer levels were low (57.7%) and high (43.3%). In non-comorbid COVID-19 patients, D-Dimer levels were low (76.7%) and high (23.3%). The Mann Whitney test obtained a result of 0.007 which means there is a significant difference. Conclusion: In the Mann Whitney test, results were obtained with the conclusion that there was no significant difference between D-Dimer levels in comorbid and non-comorbid COVID-19 patients with a P value of 0.007.